Investigating the Prevalence and Impact of Dental Phobia on Quality of Life - Dr Farwa Ghulam; Dr. Madiha Sattar; Dr Khaliqa-tul-Zahra; Wajeeha Jabeen; Dr Fouzia Aslam; Dr. Ali Anwer (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Dental phobia, a severe form of dental anxiety, is a prevalent psychological condition that leads to avoidance of dental care and contributes to deteriorating oral health, particularly among middle-aged adults. Its impact extends beyond oral health, significantly affecting overall quality of life. Understanding the prevalence and consequences of dental phobia is critical to developing effective patient-centered care strategies. Objective: This study aimed to investigate the prevalence of dental phobia among middle-aged adults and assess its impact on oral health-related quality of life (OHRQoL), with a focus on how fear and avoidance behaviors predict quality of life outcomes. Methods: A cross-sectional study was conducted between January and March 2024 in public and private dental clinics. A total of 150 adults aged 30–55 years were recruited using consecutive sampling. Data collection involved a structured self-administered questionnaire incorporating the Modified Dental Anxiety Scale (MDAS), selected items from the Dental Fear Survey (DFS), and the Oral Health Impact Profile-14 (OHIP-14). Statistical analyses were performed using IBM SPSS Statistics version 29. Pearson correlation was used to assess relationships between variables, while multiple linear regression evaluated the predictive role of dental fear and avoidance on OHIP-14 scores, controlling for age, gender, and frequency of dental visits. Results: The prevalence of moderate to high dental fear was notable, with a mean MDAS score of 14.2 ± 4.5 and DFS score of 18.6 ± 5.2. Participants reported compromised OHRQoL (mean OHIP-14 = 24.5 ± 8.3). Significant positive correlations were observed between dental fear, avoidance behaviors, and OHIP-14 scores (r = 0.65 to 0.72, p < 0.001). Regression analysis showed that both dental fear (β = 0.52, p < 0.001) and avoidance behavior (β = 0.38, p < 0.001) were strong predictors of reduced quality of life, while frequent dental visits were associated with better outcomes (β = -0.18, p = 0.013). Psychological discomfort and physical pain were the most affected domains. Conclusion: This study highlights the high prevalence of dental phobia in middle-aged adults and its significant negative impact on quality of life. Addressing dental fear and avoidance through early intervention and promoting regular dental attendance are essential to improve oral and overall well-being.